Molecularly diverse lonazolac-inspired pyrazole-cyanopyridin-2-one conjugates: design, synthesis, in vitro, in vivo and in silico studies as multi-target anti-inflammatory agents - Marwa A. Aziz; Azizah M. Malebari; Tarek S. Ibrahim; Mohamed F. Radwan; Deiaa E. Elsayed Abouzed; Rasha M. Allam; Majed Alharbi; Ahdab N. Khayyat; Gamal El-Din A. Abuo-Rahma; Mamdouh F. A. Mohamed (Molecular Diversity, 2026)

Wound healing potential by scratch assay and new flavone glycoside of Jacaranda ovalifolia R. Br. flowers - Sara Abd-Eltawab Makhlouf Mohammad; Miada Fouad Abdelwahab; Mamdouh Nabil Samy; Katsuyoshi Matsunami; Ashraf Nageeb Elsayed Hamed (South African Journal of Botany, 2026)

The impact of heavy metal pollution: bioaccumulation, oxidative stress, and histopathological alterations in fish across diverse habitats - Eman Zahran; Al-Zahraa Mamdouh; Samia Elbahnaswy; Mai M. A. El-Son; Engy Risha; Ashraf ElSayed; Manal Ibrahim El Barbary; Mahmoud G. El Sebaei (Aquaculture International, 2025)
Heavy metal contamination of aquatic environments threatens fish health and ecosystems. This review examines the bioaccumulation patterns, toxicity mechanisms, effects of oxidative stress, and histopathological changes induced by heavy metals in various fish species across different habitats. Important heavy metals, including mercury, cadmium, lead, arsenic, chromium, copper, and iron, are discussed. These metals can bioaccumulate in fish tissues via waterborne and dietary exposure, and bioaccumulation depends on several factors such as metal type, fish species, and exposure conditions. The generation of reactive oxygen species is one of the main reasons why heavy metals exert their toxic effects; depletion of antioxidants and damage to cellular components lead to oxidative stress. Oxidative stress is induced by alterations in antioxidant enzymes and increases in lipid peroxidation levels. Histopathological changes were recorded in target organs, such as the gills, liver, and kidneys. We emphasize the existing knowledge gap, which requires further research to provide full insights into fish heavy metal toxicity, with potential implications for human consumers. Understanding the toxicity mechanisms of heavy metals in fish is the key to developing biomarkers and mitigation strategies to protect aquatic ecosystems.

A Prospective Approach for Screening of Potential Evolution of Aflatoxins in Fish and Fish Feed: Molecular and Afla Fluorometry Assays - Nada H. Eidaroos; Abdelazeem M. Algammal; Mahmoud Mabrok; Mamdouh Y. Elgendy; Mahmoud E. Elsayed; Eman M. El-Diasty; Sara M. El-khamisy; Reham M. El-Tarabili (Current Microbiology, 2025)

The supplementation of dietary black cumin (Nigella Sativa) seeds on performance, blood hematology, post-metabolic responses, antioxidant status, immunity, and inflammatory markers in pre-weaning calves - Mamdouh Elsayed; Khaled M. Al-Marakby; Sabry Abdel Hafez; Sameh A. Abdelnour (Tropical Animal Health and Production, 2025)
Pre-weaning feeding is critical for calf growth, laying the foundation for future productivity and health. Nigella sativa seeds (NS) are rich in bioactive compounds with numerous beneficial effects on health and various pharmacological properties. This study aimed to investigate the supplementation of NS powder on performance, post-metabolic attributes, immunity, antioxidant capacity, and inflammatory responses in pre-weaning Friesian calves. Twenty-four Friesian male calves at 4 days of age with a similar genetic line, weighing 33.67 ± 0.6 kg, were randomly allocated to three groups (8 animals per group). The study comprised three groups: a control group (NS0) receiving no supplementation, and two experimental groups received either 1% (NS1) or 3% (NS3) NS supplementation for 84 days. All levels of NS supplementation significantly improved the final body weight and body weight gain in a linear manner ( P < 0.001), while the highest total dry matter intake was observed in NS1 group (quadratic; P < 0.001). White blood cells (quadratic, P = 0.026), lymphocytes (quadratic, P = 0.012), and monocytes (linear effect; P = 0.001) significantly decreased, whereas red blood cells (linear; P = 0.004), hematocrit (linear; P = 0.002), mean corpuscular volume (MCV, linear; P = 0.003), and mean corpuscular hemoglobin concentration (MCHC, quadratic, P = 0.007), platelets (linear; P < 0.001) increased in calves fed NS. Feeding calves diets supplemented with NS led to a significant linear decrease in plasma creatinine and liver enzymes (AST and ALT) compared to the control diet ( P < 0.01). Calves fed 3% of NS in their diets had lower plasma cholesterol (linear; P < 0.001) and triglyceride levels (linear; P = 0.002) compared to calves in NS0 and NS1 groups. Polynomial analysis indicated a quadratic decrease in direct bilirubin ( P = 0.006), and a quadratic increase in immunoglobulin G (IgG, P = 0.014) and M (IgM, P = 0.032) in the calves fed the NS diet. All NS-supplemented groups showed a significant increase in IL-10 (linear; P < 0.001), TAC (linear; P = 0.006), and CAT (linear; P < 0.001), and a significant decrease in IL-4 levels (linear; P < 0.001) of the plasma of pre-weaning calves. As expected, pre-weaning calves fed diets containing NS (1% or 3%) exhibited a quadratic decrease in plasma malondialdehyde (MDA, P < 0.001) levels compared to those fed diets without NS. Our findings suggest that incorporating up to 3% Nigella sativa into pre-weaning calf diets can enhance growth, bolster immune function, and mitigate oxidative stress, offering a promising strategy for improving health and sustainability on dairy farms.

Isolation and structural characterization of phytoconstituents from leaves of Bignonia binata - Mamdouh Nabil Samy; Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Sachiko Sugimoto; Katsuyoshi Matsunami; Mohamed Salah Kamel (Natural Product Research, 2024)

Usage of natural wastes from animal and plant origins as adsorbents for the removal of some toxic industrial dyes and heavy metals in aqueous media - Afnan S. Batubara; Hamad M. Adress Hasan; Mohammed A. Abel Moniem; Mamdouh S. Masoud; Alaa-Eldin R. Mostafa; Mohammed Gamal; Mohamed A. Elsayed (Journal of Water Process Engineering, 2023)

LC-MS-based identification of bioactive compounds and hepatoprotective and nephroprotective activities of Bignonia binata leaves against carbon tetrachloride-induced injury in rats - Mamdouh Nabil Samy; Ashraf Nageeb Elsayed Hamed; Basma Khalaf Mahmoud; Eman Zekry Attia; Usama Ramadan Abdelmohsen; Michael Atef Fawzy; Mina Ezzat Attya; Mohamed Salah Kamel (Natural Product Research, 2022)

Utilization of Landsat-8 (OLI) Image Data for Geological Mapping of the Neo-Proterozoic Basement Rocks in the Central Eastern Desert of Egypt - Mostafa Kamel; Mamdouh M. Abdeen; Mostafa M. Youssef; Ahmed M. Orabi; Elsayed Abdelbaky (Journal of the Indian Society of Remote Sensing, 2022)

Metabolomic profiling and biological investigation of Tabebuia Aurea (Silva Manso) leaves, family Bignoniaceae - Basma Khalaf Mahmoud; Ashraf Nageeb Elsayed Hamed; Mamdouh Nabil Samy; Usama Ramadan Abdelmohsen; Eman Zekry Attia; Michael Atef Fawzy; Rana Hosny Refaey; Mohammad Alaraby Salem; Sheila Marie Pimentel-Elardo; Justin R. Nodwell; Samar Yehia Desoukey; Mohamed Salah Kamel (Natural Product Research, 2021)